Pembelajaran Ekspositori: Pendekatan Efektif Untuk Meningkatkan Pemahaman Siswa Dalam Proses Pembelajaran - Najwa Najwa; Ruri Angreni; Marcela Arruan Payung Allo; Gloria Tiku Rara; Sitti Sarminah Nasir; Nur Alfadiah Syafri (PT. Citra Media Publishing, 2025)
Expository is a type of writing that aims to provide an in-depth and clear explanation of a topic, with an emphasis on facts and analysis. Expository articles avoid personal views and use a logical and organized writing structure, so that readers can easily understand the content. This type of article is often found in scholarly journals, textbooks, and mass media, and usually covers a variety of topics such as social issues, technology, science, and culture, all of which are based on relevant evidence and data. Expository writing requires skills in organizing ideas clearly, managing data accurately, and presenting arguments objectively. This article will explain the basic principles of expository writing, including its structure, writing style, and how to effectively convey information to readers. As an informative form of writing, expository helps readers understand the topic better without the influence of the writer's personal views.